Estimating the effects of Covid-19 and 5G in the submarkets of internet and mobile shopping - Seungmi Yang; Youngsun Kwon (International Telecommunications Society (ITS), 2021)
This paper aims to examine how two recent external shocks-the Covid-19 pandemic and 5G services-are transforming online shopping submarkets in Korea by estimating the effects of these two shocks on mobile shopping sales and conversion, which refers to substitution for shopping over fixed internet (termed internet shopping). Key findings are: Covid-19 boosted sales in 14 mobile shopping submarkets and decreased sales in two submarkets; 5G services also helped sales increases in 13 submarkets, while mobile technologies altogether contributed to sales increases in 14 submarkets; and mobile shopping conversions in online shopping submarkets have been driven mostly by mobile technologies, including 5G, and not by Covid-19.
Keywords: 330; Covid-19; 5G; Mobile; Online; Shopping; Conversion